2019
DOI: 10.1080/14786419.2019.1586693
|View full text |Cite
|
Sign up to set email alerts
|

Globrauneine A–F: six new triterpenoid esters from the leaves of Globimetula braunii

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Column chromatography (CC) was performed on Merck SiO2 (70-230 mesh) and Sephadex LH-20, while 1 mm thin glass plate of Merck SiO2 60 F254 (20 × 20 cm) were used for preparative thin layer chromatography (PTLC). The 1 H and 13 C NMR were recorded on a Bruker Avance 400 spectrometer operating at ambient temperature. Deuterated chloroform (CDCl3) and acetone (CD3COCD3) obtained from Sigma Aldrich were used for the NMR analysis.…”
Section: General Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Column chromatography (CC) was performed on Merck SiO2 (70-230 mesh) and Sephadex LH-20, while 1 mm thin glass plate of Merck SiO2 60 F254 (20 × 20 cm) were used for preparative thin layer chromatography (PTLC). The 1 H and 13 C NMR were recorded on a Bruker Avance 400 spectrometer operating at ambient temperature. Deuterated chloroform (CDCl3) and acetone (CD3COCD3) obtained from Sigma Aldrich were used for the NMR analysis.…”
Section: General Experimental Proceduresmentioning
confidence: 99%
“…In Nigeria, G. braunii are said to be effective against cholera, hypertension, diabetes, blood purifier, cancer, gastro-intestinal tract diseases and wound infections [10][11][12]. Our previous phytochemical studies on G. braunii have successfully isolated several triterpenoid esters [13], lactones and flavonoids [14]. We also reported that, the ethyl acetate extract of G. braunii has the ability to protect mice at dose of 150 mg/kg against pentylenetetrazole induced seizure by 83.33% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Pure MTX showed symmetrical and asymmetric tensile vibrations of COO-(νCOO-) at 1373 and 1554 cm -1 , respectively [31]. The absorption peaks of triterpenoids in the spectrum are mainly at 1050 cm -1 (-OH group), 1740 cm -1 to 1760 cm -1 (fivemembered cyclic ketone), 1720 cm -1 (ester), 1710 cm -1 (six-membered ring) Ketone), 1650 cm -1 (α, βunsaturated ketone) [32]. In the spectrum of CEFSM the peak positions of triterpenoids changed.…”
Section: Ftir Spectroscopy and Xrd Analysismentioning
confidence: 99%
“…The hepatic, hematologic, anti-lipidemic, oxytocic, anti-hyperglycemic and anti-cancer activities of the plant's alcoholic, aqueous and ethyl acetate extracts have also been reported [5,6,[10][11][12] with a paucity of information on its chemistry. Preliminary phytochemical reports showed that the plant contained phenolics, terpenes, flavonoids and sterols, while compounds, such as globrauneine A-F, lupeol, lupeol palmitate, β-sitosterol, friedelin, octanoic acid, lactones and flavonoids (quercetin, quercitrin, catechin, rutin and avicularin) have been reported in the plant [13,14].…”
Section: Introductionmentioning
confidence: 99%